Analysis of Arabic-Indonesian Translation Errors on Google Translate - Kusuma, Eka Dian; Yulia, Fatma (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to analyze the results of Google Translate machine translation in translating Arabic into Indonesian. The data of this study used primary data types in the form of literature from books with library sources were Arabic texts taken from the book Nurul Yaqin written by Sheikh Muhammad Al Khudari Bek and his translation books in Indonesian and taken by random sampling technique. This research uses a qualitative approach with a descriptive qualitative type. This study aims to analyze the results of machine translation google translate in translating Arabic into Indonesian. This research is related to translation, namely the process of translating from Arabic into Indonesian by looking at the process carried out by Google Translate and then analyzing the results of the translation. The primary data is in the form of Arabic texts taken from the book Nurul Yaqin written by Sheikh Muhammad Al Khudari Bek. Then the author takes researched from the subtitles in the book, namely, the cleavage of the breast of the Prophet Muhammad SAW. The focus of this research is to find out what translation errors are focused on the linguistic level, such as morphology, syntax, and semantics. In this study, the authors identified errors at the morphological, syntactical, and semantic levels contained in google translate from Arabic to Indonesian. By using error analysis (error analysis) with procedures, 1) collecting error samples, 2) identifying errors, 3) explaining errors, 4) classifying errors, and 5) evaluating errors. The results of the study show that in terms of the accuracy of vocabulary and terms, google translate has good translation quality. In terms of clarity and reasonableness, it means that Google Translate has not been able to convey ideas from the source language into the target language. Furthermore, grammatically, the results from Google Translate translation do not have grammar, then the results from Google Translate translation do not have a good grammatical structure and follow the rules that apply in the target Indonesian language. From these data, it can be seen that Google Translate should not be used as a basis for translating Arabic texts into Indonesian. A novice translator should prefer a dictionary instead of using Google Translate to try and improve their translation skills. So far, Arabic is still a difficulty for Indonesians, especially for students, and this difficulty is a linguistic problem that includes phonology, syntax, morphology, and semantics.